2010
DOI: 10.1021/jp909927w
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding Effects on the Reorganization Energy for Photoinduced Charge Separation Reaction between Porphyrin and Quinone Studied by Nanosecond Laser Flash Photolysis

Abstract: Alcohol concentration dependences of photoinduced charge separation (CS) reaction of zinc tetraphenyl-porphyrin (ZnTPP) and duroquinone (DQ) were investigated in benzonitrile by a nanosecond laser flash photolysis technique. The photoinduced CS reaction was accelerated by the addition of alcohols, whereas the addition of acetonitrile caused little effect on the CS reactions. The simple theory was developed to calculate an increase in reorganization energies induced by the hydrogen bonding interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…Specifically, whereas Δ G CR increases from −1.54 to −1.29 eV when going from pure CH 2 Cl 2 to pure HFIP (see above), the reorganization energy ( λ ) may increase simultaneously. Prior investigations on related quinone systems demonstrated that hydrogen bonding between alcohols and quinone anions can lead to a significant increase of λ 14a. 17 The precise change of λ (in eV) in our system cannot be determined from the available experimental data.…”
Section: Methodsmentioning
confidence: 88%
“…Specifically, whereas Δ G CR increases from −1.54 to −1.29 eV when going from pure CH 2 Cl 2 to pure HFIP (see above), the reorganization energy ( λ ) may increase simultaneously. Prior investigations on related quinone systems demonstrated that hydrogen bonding between alcohols and quinone anions can lead to a significant increase of λ 14a. 17 The precise change of λ (in eV) in our system cannot be determined from the available experimental data.…”
Section: Methodsmentioning
confidence: 88%
“…[2][3] There have been numerous investigations of photoinduced electron transfer in artificial porphyrin-benzoquinone dyads mimicking the function of the P680 primary donor and the QA primary acceptor in biological systems, [4][5] but the influence of hydrogen bond donors on the thermodynamics and kinetics of quinone reduction has received comparatively little attention in such studies. [6][7][8][9][10][11]12 The present work provides more insight into the effects of hydrogen bonding on quinone reduction via long-range electron transfer from distant photoreductants.…”
Section: Introductionmentioning
confidence: 81%
“…From the discussion above we conclude that in the case of the reference complex and the two longer dyads (n = 2, 3) quenching by HFIP occurs directly at the Ru(bpy)3 2+ unit through increasingly efficient multiphonon relaxation, whereas in the case of Ru-xy1-AQ a significant extent of quenching occurs indirectly through increasingly efficient intramolecular electron transfer from the Ru(bpy)3 2+ roughly a factor of 3 larger than the inherent 3 MLCT decay rate constant ((659 ns) -1 = 1.5•10 6 s -1 ), consistent with the observation of significant luminescence quenching in this particular dyad in presence of HFIP.As seen above, AQ reduction in presence of HFIP is associated with a significant change in hydrogenbonding equilibrium. An interesting question is whether in the case of intramolecular photoinduced electron transfer in Ru-xy1-AQ the change in equilibrium occurs after the electron transfer event or whether there is a concerted overall reaction mechanism 11. Scheme 3 illustrates the possible reaction pathways: Initially, one HFIP molecule is weakly (Ka = 1 M -1 ) hydrogen-bonded to charge-neutral AQ (upper left panel).…”
mentioning
confidence: 99%
“…The PCET process can be defined by one of the following processes: protont ransfer-electron transfer (PT-ET), stepwisee lectron transfer-proton transfer (ETPT), or concertedp roton-electron transfer (CPET). [11] In the bacterialp hotosynthetic reaction, the fast electrontransfer process also occurs through the reduction of quinone, [12] which is facilitatedb yt he formation of aH -bonded adduct with amino acids in the immediate vicinity with appropriate spatial orientation.T he semiquinone radical, ap artially reduced form of quinone, is generally highly reactive, and decaysq uickly upon production through ac hemical transformation. [7,8] For photosynthesis, quinones playakey role as ap rimary electron acceptor, [9,10] and the reductionp rocess of quinonei sf acilitated by H-bonddonors or by protonation.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] For photosynthesis, quinones playakey role as ap rimary electron acceptor, [9,10] and the reductionp rocess of quinonei sf acilitated by H-bonddonors or by protonation. [11] In the bacterialp hotosynthetic reaction, the fast electrontransfer process also occurs through the reduction of quinone, [12] which is facilitatedb yt he formation of aH -bonded adduct with amino acids in the immediate vicinity with appropriate spatial orientation.T he semiquinone radical, ap artially reduced form of quinone, is generally highly reactive, and decaysq uickly upon production through ac hemical transformation. [13,14] In biological processes, such semiquinone radicals participate in relay processes to extend their lifetimes; this also preventss uch radicals from participating in undesired side reactions.…”
Section: Introductionmentioning
confidence: 99%